THE IMPLEMENTATION OF THE MAKASSAR CITY OMBUDSMAN DUTIES IN FOLLOWING UP ON MALADMINISTRATION CARRIED OUT BY THE REGIONAL APPARATUS ORGANIZATION - ANDI BAU MEDLIN AR; HAMZAH HALIM; ZULKIFLI ASPAN (Awang Long Law Review, 2021)
This paper analyzes the implementation of the Makassar City Ombudsman duties in following up on maladministration carried out by Regional Apparatus Organizations. This type of research is empirical legal research, 2 (two) types of legal materials that the author uses, namely primary legal materials and secondary legal materials. The data obtained both primary and secondary were analyzed qualitatively and presented descriptively. The results showed that the implementation of the Makassar City Ombudsman Duties in following up on Maladministration at Regional Apparatus Organizations, especially those that occurred at the Department of Population and Civil Registration had been carried out, but was not optimal, because there were still reports related to the same thing that were submitted to the Makassar City Ombudsman in the following year, namely In 2019 to 2020, this means that the Makassar City Ombudsman still needs to improve supervision to prevent maladministration at the Makassar City Education Office and the Makassar City Population and Civil Registry Office regarding the same things that have happened before in the same place.